CONVERSATIONAL IMPLICATURE IN “UPGRADED” MOVIE - Tanjung Abady, Suryany; Kurniawan, Yulius; Rachmawaty Linuwih, Endar (Indonesian Journal of Linguistics, 2025)
Effective communication is an essential aspect in the workplace to ensure that implied meanings are well understood and potential misunderstandings are reduced. This study aims to identify the types of non-observance maxims, how the non-observance maxim occurs, and the types of conversational implicatures in the dialogues of the main character in the Upgraded movie, which is set in a workplace context. The analysis of conversational implicature is based on Grice's theory, while the classification of non-observance maxim refers to Thomas’s theory. This research employs a descriptive qualitative method, with the data collected by watching the movie and transcribing utterances containing conversational implicatures. The validity of the data was strengthened through triangulation. The findings reveal that conversational implicatures emerge through various forms of maxim non-observance, including 13 instances of flouting the maxim of quality, 2 maxim of quantity, 4 maxim of relevance, 2 maxim of manner, and 5 instances of violating the maxim of quality. In addition, the study identified 19 particularized conversational implicatures and 7 generalized conversational implicatures. These findings indicate that maxim non-observance is not merely a form of deviation but also a communication strategy that helps construct conversational implicatures, thereby providing new insights into workplace communication patterns.